Droplet distribution and mitigation of occupational exposure risk in eucalyptus sprout eradication using a remotely piloted aircraft - Felipe Oliveira Ribeiro, Luis; Leandro da Vitória, Edney; Pereira Bastos, Halisson; Vieira Zanelato, Jacimar; de Assis Martins Júnior, José; de Vicente Ferraz, Alexandre; Gomes dos Santos, Thales; de Assis Ferreira, Francisco; Victor Oliveira Ribeiro, João; de Assis Silva, Samuel; Chen, Pengchao (Frontiers in Plant Science, 2025)
The use of remotely piloted aircrafts (RPAs) for foliar application of pesticides and fertilizers has increased worldwide in several agricultural crops. However, there is little information on the efficiency and factors connected to application and spraying quality of RPAs in forestry, mainly for eradication of eucalyptus sprouts. The objective of this work was to evaluate droplet distribution and deposition on eucalyptus sprouts and the risk of exposure for applicators using an RPA (DJI AGRAS T40) at different theoretical application ranges (7.0, 9.0, and 11.0 m) and droplet sizes (150, 300, and 450µm) compared to a manual electric backpack sprayer (MEBS). The spray solution was composed of water, brilliant blue dye, and adjuvant. Water-sensitive paper cards and flexible polyvinyl chloride cards were positioned on different eucalyptus sprout canopy layers (ESCL) (upper, middle, and lower) to evaluate droplet distribution and deposition. Disposable coveralls, gloves, and respirators were used to evaluate the risk of occupational exposure. The results showed that the application ranges of 7.0 and 9.0 m with droplet sizes of 150µm and 300µm resulted in better droplet distribution throughout the ESCLs. However, the 450µm droplet size resulted in concentration of droplets in the upper ESCL. Using an MEBS resulted in greater heterogeneity in droplet distribution and approximately a 160-fold higher accumulation of droplets on different applicator’s body parts compared to the RPA. The results confirmed the efficiency and operational safety of using RPAs for the application of agricultural pesticides and foliar fertilizers in eucalyptus plantations, as well as providing valuable contributions for future research on these practices in eucalyptus cultivation.